TRADISI BAJAPUIK PADA PERKAWINAN MASYARAKAT PARIAMAN DI KELURAHAN TUAH KARYA KECAMATAN TAMPAN KOTA PEKANBARU - Laila Istiqamah; Yusmar Yusuf (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2018)
This research was conducted sub-district Tuah Karya, Tampan districts, city ofPekanbaru. Background raises the issue of bajapuik tradition At Pariaman societymarriage sub-district Tuah Karya e, Tampan Districts, City of Pekanbaru is becausethe implementation of marriage is one of the cultures that follow the development ofhuman culture in the life of the society. Culture of marriage and its rules that apply inthe society and society environment can not be separated from the influence of cultureand environment where society is located as well as social interaction that is influencedby science, experience, trust and others. In the present implementation of the traditionexperienced a change that can not be separated from the modernization and sciencethat led to changes in the mindset of the society to think more practically, so that thecharacteristics of society and the implementation of the tradition began to be neglectedThis undergraduate thesis aims to analyze the extent of Pariaman society in theoverseeing preserving bajapuik tradition in the background of various cultures ofoverseas by looking at how the process of implementation of the bajapuik tradition andhow the society view about the implementation of bajapuik tradition in the overseas.This research is a qualitative research with descriptive approach. The data usedin the form of primary and secondary data. Technique of data collecting done byobservation method, interview and literature study which all answer problem inresearch about implementation of bajapuik tradition of Pariaman society at TuahKarya District, Tampan, city of Pekanbaru. The informants of this research arePariaman overseas society consisting of adat leaders, niniak mamak, brides who carryout the bajapuik tradition at Tuah Karya District and the head of the Office of ReligiousAffairs (KUA) in Tampan.Based on the results of research, it is found that the implementation of thistradition is flexible, not burdensome and also difficult, so there are some people ofPariaman who implement and some do not implement. In the implementation oftradition also found not all processes implemented as implemented in the region oforigin. As for the background of the emergence of bajapuik tradition are: (1) the fear ofgirls not getting a partner (2) the matrilineal kinship system adopted by the community,thus making the Bajapuik Tradition an implementation of the Matrilineal kinshipsystem, in which the heritage is established to belong to women, while the men getnothing.Keywords : Tradition, Bajapuik, Pariaman Overseas